2008 IEEE International Conference on Services Computing 2008
DOI: 10.1109/scc.2008.53
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying Service Deployment with Virtual Appliances

Abstract: As IT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…We evaluated the effect of procedural and declarative constraints on the runtime of the planner and found that procedural constraints can achieve constant runtime for placement constraints in the presence of highly loaded data centers. For future work we would like to extend our approach to other examples besides the deployment case study, to apply it to Virtual Appliances [12], and to examine how configuration aspects [14] can be addressed using the notion of state-transition systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the effect of procedural and declarative constraints on the runtime of the planner and found that procedural constraints can achieve constant runtime for placement constraints in the presence of highly loaded data centers. For future work we would like to extend our approach to other examples besides the deployment case study, to apply it to Virtual Appliances [12], and to examine how configuration aspects [14] can be addressed using the notion of state-transition systems.…”
Section: Discussionmentioning
confidence: 99%
“…(6) The knowledgebase can be easily adapted to take different solutions for application deployment into account. For example, solving deployment using Virtual Appliances [12], [13] or using a finer grained domain comprising installation and configuration of applications [14]. The remainder of this paper is organized as follows: Section II introduces our notion of models and state-transition systems.…”
Section: Saas -Iaas Constraintsmentioning
confidence: 99%
“…To tackle the aforementioned problems, we propose an automated, logically sound approach to adapt IT change plans to changed management domains to render infeasible change plans executable. We show the feasibility of our approach by applying it to a network configuration and deployment case study of a 2-tier architecture using virtual appliances [8], [9]. Using our case study we show that our randomized approach scales nicely regarding performance penalties for different types of unpredictable changes, even for large, heavily (85%) loaded data centers in 95% of all cases.…”
Section: Introductionmentioning
confidence: 90%
“…mem free >= g i p v ( " vmem " ) } ) 8 p r e ( " enough cpu " , { g i p v ( " pm " ) . c p u f r e e >= g i p v ( " vcpu " ) } ) 9 p r e ( " pm r u n n i n g " , { g i p v ( " pm " ) .…”
Section: Parameter Enhanced It Change Plansmentioning
confidence: 99%
“…Services can be deployed in virtual machines (VMs) [4] [5]. These virtual machines are isolated from each other but can multiplex the same underlying hardware resources.…”
Section: Introductionmentioning
confidence: 99%